Skócia és Anglia – reform a tisztességtelen kereskedelmi gyakorlatok terén - Tárczy, Edit Zsuzsanna (Debreceni Jogi Műhely, 2011)
After the implementation of the 2005/29/EC Directive on unfair commercial practices (hereafter: UCPD) in the United Kingdom is has been discovered that the misleading and the aggressive practices are targeting many people. Some of them moreover damage the reputation of the traders who act legally, and the reputation of the market.So, the Scottish Law Commission and the Law Commission for England and Wales want to create a new system on remedies. Because of this aim the two commission started a consultation in April, it ended in July. Presently, The Consumer Protection from Unfair Trading Regulations 2008 (hereafter: CPRs) – which was one of the regulations which have implemented the rules of the UCPD – contains rules on the liability for unfair commercial practices, and - according to the rules – the realization of the practices is an offence.But in respect of civil law the rules don’t have unity: the rules of misrepresentation are applied in the case of misleading practices, but in the case of aggressive practices there aren’t rules.The two commissions want to create a new consumer protection act, which will complete the rules of the CPRs. In this act there will be two levels of remedies:on the first level the main aim will be the restoration of original condition (before the contract)on the second level the main aim will be the compensation.The commissions hope that after the reform the following will be:because of the clearer rules the claims will become more successfulbecause of the clearer rules the traders’ - who are acting legally - costs will decreasethe costs of the organizations – which are dealing with consumer protection – will decrease after the reform, and the proceedings of them – perhaps – become more successful.The two commissions will publish the data from the consultation in March 2012.